Number System Conversion for Beginners (Decimal to Binary, Octal and Hexadecimal Conversion) - Dr. Ms. Shabnam S. Mahat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A number system is the method or system of representing the digits in the computer system. The total number of digits used in a number system is called its base or radix. The base is written after the number as subscript; for example  Binary number system (Base 2), like 10010(2) (10010 base 2).  Octal number system (Base 8), like 76(8) (76 base 8).  Decimal number system (Base 10), like 521(10) (521 to base of 10).  Hexadecimal number system (Base 16), like 5AE (16) (5AE to base of 16). This paper discusses the decimal to binary, decimal to octal and decimal to hexadecimal conversion that will be useful for digital computers, and the field of computer science.